Dance of the Jakaranda - Kimani, Peter, 1971- (KENYA PRESTIGE, 2017)
Set in the shadow of Kenya's independence from Great Britain, this story reimagines the special circumstances that brought black, brown, and white men together to lay the railroad that heralded the birth of the nation.--
Keywords: 1895-1963; Friendship -- Fiction; Race relations -- Fiction; Identity (Psychology) -- Fiction; Railroad construction workers -- Kenya -- Fiction; FICTION / African American / General; FICTION / Cultural Heritage; Friendship; Identity (Psychology); Race relations; Railroad construction workers; Kenya -- History -- 1895-1963 -- Fiction; Kenya; Historical fiction; Fiction; History; Historical fiction; Historical fiction